A pelican in the wilderness : hermits and solitaries - Colegate, Isabel (Washington, D.C. : Counterpoint, 2002)
"The desire for solitude is as old as human society, its pursuit as various as the individual temperament. From Lao Tsu and the Buddha, St Antony and the early Celtic hermits, through Rousseau, Thoreau, Ruskin and Thomas Merton, certain gifted persons, each in his own way, have shown a vocation for living alone and apart, finding in simplicity and attention to Nature a spiritual space to be explored and rejoiced in.
Others, retreating from the world in scorn or cut off from it by scandal, have found that solitude is Hell, a pit of melancholy and morbid fantasy." "In this book, Isabel Colegate gives us the lives of the solitaries - male and female, mediaeval and modern, divinely inspired and merely eccentric."--BOOK JACKET.
Includes bibliographical references (p. 267-274) and index.
Keywords: Hermits; Solitude